Analysis Of Factors Affecting Purchase Decisions At National Scale Services And Local Kaur District - Irlis Suanto; Neri Susanti; Eska Prima Monique (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2021)
The purpose of this study was to determine the factors that influence purchasing decisions at the National and Local Scale Supermarkets of Kaur Regency. The sample in this research is 95 consumers. The sampling technique used saturated samples, namely by using the entire study population as the research sample. Methods of data analysis using quantitative methods, namely by using multiple linear regression analysis. The results prove that social class, price, promotion, service quality and location variables have a significant influence on the dependent variable, namely purchasing decisions at the national and local scale supermarkets of Kaur Regency, and promotion has no effect on purchasing decisions on the local scale of Kaur Regency.